The impact of the Russia-Ukraine war on the Russian supply chain - Neha Bargujara; Muhammad Ahmed Kalwar; Ioannis Dermitzakis; Asif Nawaz (Journal of Emerging Science and Engineering, 2025)
The Ukraine and Russia war has damaged the worldwide supply chains during the war, several countries imposed dozens of sanctions worldwide which crippled the supply chain of Russia to a great extent. In many nations, bans were also imposed on industrial products, fossil fuels, raw materials, and grains. In this regard, the authors have analysed how the war between Ukraine and Russia has affected the supply chain of Russia, and that analysis is presented in this dissertation. The findings presented by this research have indicated that finished goods, fuels, and energy shortages have augmented inflation. The war affected the routes of transport which in turn impacted the goods and logistics of the commodities by Russia. Due to war, Europe has taken the step to welcome the Russians leaving their country. The sanctions imposed have adversely affected the Russian imports from Europe and exports to Europe. However, European countries such as Poland, Germany, and Finland imported natural gas from Russia and the imports of fossil fuels were increased by nations like Turkey, China, and India. In this way, Russia's earnings from its sales of fossil fuels rose. Unfortunately, everything gets costly because the cost of transport increased, and worldwide prices of energy elevated. Intense inflation was led by this war.